When Is Less More? Boundary Conditions of Effective Entrepreneurial Bricolage. (April 2023) - Steffens, Paul Richard; Baker, Ted; Davidsson, Per; Senyard, Julienne Marie
Abstract : While prior research suggests that entrepreneurial bricolage is often useful as a coping mechanism for resource-constrained new ventures, other accounts document detrimental effects of bricolage. As the conditions for effective bricolage have not been systematically examined in prior research, we develop and test theoretical explanations for some important boundary conditions. We propose that while bricolage has a positive influence through a resource replacement mechanism, it may be detrimental through the intertwined "second-best solutions" and "tinkering trap, " which together lead to an accumulation of compromises that may result in a detrimental path dependence. We hypothesize that the intensity of these counteracting mechanisms differs depending on the venture's stage of development (nascent vs. operational) and its level of growth expectations. In essence, we argue that ventures expecting to achieve more derive greater benefit from resource replacement. In addition, they are more likely to resist an accumulation of compromises. We test our hypotheses using a longitudinal study of early-stage ventures. Although the results mostly support our theory, they also point to one interesting surprise for which we extend our theorizing to propose an explanation. Counter to the prevailing view in the literature, we find that bricolage is particularly effective for developing competitiveness for early-stage ventures striving to develop and grow. Complementing this, our results suggest the net effects of bricolage may actually be detrimental to the competitiveness of operational ventures that are not actively trying to grow.